2018
DOI: 10.1590/1809-4430-eng.agric.v38n6p813-823/2018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Fuzzy Inference Systems to Predict the Surface Temperature of Broiler Chickens

Abstract: This study aimed to compare fuzzy systems with different configurations to predict the surface temperature (ts) of broiler chickens subjected to different intensities and durations of thermal challenges in the second week of life. Data on the ts of broiler chickens aged 8 to 11 days were acquired by infrared thermography and subjected to combinations of four dry-bulb temperatures (tdb) (24, 27, 30, and 33 ºC) and four durations of thermal challenges (DTC) (1, 2, 3, or 4 days). The input variables of the fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The output of the buck converter is given as V out = D.V n , where D = duty cycle assuming a 16% duty cycle with V in = 76 V and V out = 12 V. The output current I out = V out /R. The inductance of the buck converter is presented in Equation (26).…”
Section: Buck Converter Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The output of the buck converter is given as V out = D.V n , where D = duty cycle assuming a 16% duty cycle with V in = 76 V and V out = 12 V. The output current I out = V out /R. The inductance of the buck converter is presented in Equation (26).…”
Section: Buck Converter Designmentioning
confidence: 99%
“…The primary challenge posed by the proposed technique is the movement of the receiver coil due to the changing load. This can be resolved by using a high-level control to enhance the efficiency of the power transfer [24][25][26]. Moreover, with the intention of improving its action, the shape of the transmitter coil can be designed to be circular or rectangular [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed the Ts changes with air temperature (Ta) and relative humidity (RH). An increase in Ta and RH increases the Ts of broilers of age 1-35 d [21][22][23]. The Ts variation with all these environmental factors was assessed for the birds of age up to 42 d. Hence, although Ts can be used as an indicator of stress, the evaluations are not available for heavier and bigger birds of current market size.…”
Section: Introductionmentioning
confidence: 99%
“…Since Ts is useful in assessing the thermal stress of broiler chickens [18,21], several approaches were taken to build models and methods that can be easily used to practically predict the Ts of broilers [20,23,28]. However, limitations in Ts measurement, changes of Ts with the environment, and variations of Ts at various ages underestimated the Ts of broiler chicken.…”
Section: Introductionmentioning
confidence: 99%
“…The concepts of fuzzy logic are applied in principles that traditional logic does not allow explanations. Together, the fuzzy theory makes it possible to perform reasoning close to that of human beings in environments with uncertainties (Senna et al, 2015, Raj & Mohan, 2016, Sousa et al, 2006 The use of fuzzy theory is used in several areas of knowledge, such as in the poultry area, in modeling the impacts generated on the surface of the broiler by different temperatures (Bahuti et al, 2018), in the sphere of medicine in analyzing the need to administer vasopressors in ICU patients (Salgado et al, 2016), in the agricultural sector in obtaining reference evapotranspiration, replacing the conventional methodology (Kisi, 2013), among other compositions involving mathematical and computational methods that this logic is capable of to develop.…”
Section: Introductionmentioning
confidence: 99%